Comparative antimicrobial efficacy of oregano oil, chlorhexidine, and sodium hypochlorite against Enterococcus faecalis: An in vitro study - Kavalipurapu Venkata Teja; Krishnamachari Janani; Vasundhara Apoorva Kaligotla; Krishnamachari Harini (Endodontology, 2021)
Objective: The purpose of this study was to evaluate the comparative antibacterial efficacy of 0.2% oregano oil, 2% chlorhexidine (CHX), and 3% sodium hypochlorite (NaOCl) in disinfection of dentin tubules contaminated with Enterococcus faecalis. Materials and Method: One hundred and twenty human extracted anterior teeth were infected with E. faecalis for 21 days. They were assigned into three groups (n = 40) – Group 1: 3% NaOCl, Group 2: 2% CHX, and Group 3: 0.2% oregano oil. Disinfection protocol was followed using 31-gauge side-vented needle. After chemomechanical preparation, the apical 5 mm of the roots was removed frozen in liquid nitrogen and pulverized to expose E. faecalis in dentinal tubules. The number of colony-forming units of E. faecalis per mg dentin was determined. The data were analyzed statistically. Results: Zone of inhibition of oregano oil was found to be 15 mm, and the values were significant in Group III (P < 0.05) as compared to the other groups assessed. Conclusion: Within the study's limitation, 0.2% oregano oil showed better disinfection property against E. faecalis among tested irrigants. Therefore, it can be used as an effective alternative root canal irrigant.